The Characters of Hermione Granger and Wendy Darling as Maternal Figures - Houžvičková, Tereza (Univerzita Pardubice, 2022)
The thesis deals with the depiction of maternal characteristics and feminine personality traits within the characters of Hermione Granger from Harry Potter, and Wendy Darling from Peter Pan. It is also focused on the evolution of the genre of fantasy, and provides an overview regarding the evolution of women in society as well as the feminist literary criticism. The analysis focuses on the similarities and differences depicted within the characters with special emphasis on earlier mentioned maternal and feminine traits.
Hermiona Granger a Wendy Darling jako prototypy mateřských postav
Keywords: Harry Potter; Peter Pan; Hermiona Granger; Wendy Darling; Viktoriánská Británie; fantasy; matky; ženy; Harry Potter; Peter Pan; Hermione Granger; Wendy Darling; Victorian Britain; fantasy; mothers; women